902 Safe Elective & Emergency Surgery During the COVID-19 Crisis: Experience of a Large Tertiary Centre During the First Wave of the Pandemic. (12th October 2021) - Giorga, A; Thompson, J; Lo, T; Baker, R
Abstract: Aim: In addition to a reduction in elective surgery, the COVID-19 pandemic has been associated with concerning rates of post-operative mortality in COVID-19 patients highlighting the threat of nosocomial transmission. Relocation of elective patients into a protected cold wing of a tertiary centre, vigilant testing and staff test, and trace were implemented to address these issues. Method: Retrospective analysis of 5069 consecutive patients who underwent procedures in theatre from 11/03/20 – 08/09/20 was performed. Comparison of numbers of procedures was compared with the same study dates in 2019. Detailed analysis of nosocomial transmission of COVID-19 and mortality was performed using patient notes and death certificates. Results: 5854 procedures were performed in 2020 compared with 13219 in 2019, representing a reduction of 55.7%. The overall mortality in 2020 was 2.7% (135/5069). COVID-19 negative mortality was 2.36% (119/5033). 74 patients tested positive for COVID-19 at any time (1.3%); mortality amongst patients who tested positive seven days pre- to 30 days post-procedure was 5.4% (4/74). Nosocomial transmission rate was 0.27% in elective admissions (10/3773) and 0.97% in acute admissions (20/2052). Conclusions: The first wave of the pandemic has predictably caused a significant reduction in elective activity. Our hospital infection prevention measures have kept nosocomial transmission rates low, particularly for elective admissions. We have observed lower rates of post-operative mortality in COVID-19 patients than published in other centres. Continuation of surgical services is important for patient outcomes, and essential for training the surgeons of tomorrow.